DESCRIPTIVE AND THEORETICAL ASPECTS OF ENGLISH IDIOMS (International journal of artificial intelligence, 2024)
As we know, idioms are an integral part of language, offering insight into culture, thought processes, and even humor. In this article, we will explore both the descriptive and theoretical aspects of English idioms, examining their characteristics, uses, and significance within the broader context of language study. By integrating both perspectives, we aim to provide a comprehensive overview of these fascinating expressions and their role in communication.